2002
DOI: 10.4049/jimmunol.168.7.3550
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Mechanisms Control the Retention of IL-8 in Lungs and Skin

Abstract: Chemokines are a group of structurally related peptides that promote the directed migration of leukocytes in tissue. Mechanisms controlling the retention of chemokines in tissue are not well understood. In this study we present evidence that two different mechanisms control the persistence of the CXC chemokine, IL-8, in lungs and skin. 125I-labeled IL-8 was injected into the airspaces of the lungs and the dermis of the skin and the amount of 125I-labeled IL-8 that remained at specified times was measured by sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…Although we do not know the exact physiological concentrations of these chemokines in vivo, their long t 1/2 could ensure their effectiveness in inducing ASMCs proliferation or enhancing their survival. Moreover, using a rabbit model, Frevert et al (19) have shown that IL-8 is retained in the lungs to a much higher levels than in other tissues such as the skin, and the dimerization of IL-8 plays a role in this process. Knowing that, one can predict that effective levels of IL-8 within the lung tissue could be reached upon its enhanced production and accumulation with time.…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not know the exact physiological concentrations of these chemokines in vivo, their long t 1/2 could ensure their effectiveness in inducing ASMCs proliferation or enhancing their survival. Moreover, using a rabbit model, Frevert et al (19) have shown that IL-8 is retained in the lungs to a much higher levels than in other tissues such as the skin, and the dimerization of IL-8 plays a role in this process. Knowing that, one can predict that effective levels of IL-8 within the lung tissue could be reached upon its enhanced production and accumulation with time.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we instilled 12 μg each of LukS-PV and LukF-PV (i.e., 0.34 nmol of LukS-PV and 0.32 nmol of LukF-PV), amounts comparable to that produced during USA300 infection of rabbit lungs (Fig. 2I), endotracheally into lungs of normal rabbits and neutropenic (vinblastine-treated) rabbits (32). Because both LukS-PV and LukF-PV are required for biological activity (6, 7), each toxin subunit alone was used as a negative control.…”
Section: Pvl Causes Lung Inflammation and Injury By Pmn-dependentmentioning
confidence: 99%
“…IL-8 dimerization is sensitive to solution conditions, and the reported dissociation constants (K d ) vary by as much as 160-fold (0.1-16 M), indicating that IL-8 could easily dimerize under in vivo conditions (7,8). A variety of in vitro cell-based and in vivo studies also suggest dimerization of IL-8 on binding to GAGs (9,10). IL-8 is active for GPCR function at nanomolar concentrations in in vitro cell-based assays, suggesting that IL-8 binds its receptor as a monomer.…”
mentioning
confidence: 99%